Effects of resistance training intensity on the sleep quality and strength recovery in trained men: a randomized cross-over study - Ramos-Campo, D. J.; Martinez-Aranda, L. M.; Caravaca, L. A.; Ávila-Gandia, V.; Rubio-Arias, J. A. (Biology of Sport, 2021)
Resistance training (RT) variables can affect sleep quality, strength recovery and performance. The aim of this study was to examine the acute effect of RT leading to failure vs. non-failure on sleep quality (SQ), heart rate variability (HRV) overnight and one-repetition maximum (1-RM) performance 24 hours after training. Fifteen resistance-trained male athletes (age: 23.4 ± 2.4 years; height 178.0 ± 7.6 cm; weight: 78.2 ± 10.6 kg) performed two training sessions in a randomized order, leading to failure (4x10) or non-failure (5x8(10) repetitions), with 90 seconds for resting between sets at 75% 1-RM in bench press (BP) and half squat (HS). The day after, the participants completed the predicted 1-RM test for both exercises. In addition, the subjective and actigraphic SQ and HRV during sleep were measured after each training session. The day after the training protocol leading to failure, the 1-RM of BP (MD = 7.24 kg; -7.2%; p < 0.001) and HS (MD = 20.20 kg; -11.1%; p < 0.001) decreased. However, this parameter did not decrease after a non-failure RT session. No differences were observed between failure and non-failure training sessions on SQ and HRV; therefore, both types of training sessions similarly affected the SQ and the autonomic modulation during the night after the training session. This study provides an insight into the influence of different training strategies on SQ, strength performance and recovery after moderate- to high-demand training. This information could be useful especially for professional coaches, weightlifters and bodybuilders, due to the potential influence on the programming processes.